Art en Marge : Collection. - Fol, Carine; Colin, Brigitte; Gosuin, Didier; Henrion, Françoise; Meurant, Georges; Preszow, Gerard; Thévoz, Michel (Brussel : Art en Marge a.s.b.l. - v.z.w. Brussel, 2003)
Amazine, Yassir ; Andouche, Ines ; Awa, Seyni ; Baptista, Encarnacao ; Bedenski ; Bergamashi, Umberto ; Boden, Christiane ; Bossert, Herman ; Bottemane, Dominique ; de Bruyne, Heide ; Carles-Tolra, Ignacio ; Célestin ; Chapelain, Monique Le ; Cicherski, Adam ; Convey, Tony ; Cordier, Victor ; Cornelis, Daniel ; Cosyns, Sylvain ; Crèvecoeur, Kikie ; Cycon, Kaziemierz ; Defontaine, François ; Degand, Jaqueline ; Degeyter, Thierry ; Deix, Gunther ; Delaunay, Alain ; Delaunay, Serge ; Delhaye, Michel ; Dubasin, Patrick ; Duesberg, Georges ; Duhem, Paul ; Dupuis, Bruno ; Dutkiewska, Stanislaw ; Fierens, Baudouin ; Fillaudeau, Noël ; Gilson, Fabienne ; Godard, Jean-Pol ; Godfroid, Bernard ; Godi, Jules ; Goldani, Agostino ; Gonzalez, Juanma ; Grünenwaldt, Martha ; Guischer, Anne ; Van Hecke, An ; Helmut ; Herbots, Jean-Paul ; Hervijns, Victor ; Heyligen, Jean-Marie ; Holmes, Juliette ; Jhelil, Valéry-Mehdi ; Joly, Hugues ; Kellens, Anne ; Kosek, Ryszard ; Lacoste, Alain ; Lacroix, Anne ; Lafont, Geneviève ; Lamour, Jean-Pierre ; Laurent, Françoise ; Lippstreu, Alexis ; M.C.H. ; Mackintosh, Dwight ; Marshall, Francis ; Masquelière, Pascal ; Masse, Edmonde ; Menard, Micheline ; Mills, Larry ; Mrabet, Mohammed ; Mvumbi, Antoine ; Van Nuffel, Marc ; Opiola, Krzysztof ; Outelet, Anne ; Perrot, René ; Potvliege, Anne-Marie ; Pouleva, Valentina ; Prues, André ; De Radiguès, Bernard ; Remacle, Christine ; Reyns, Fernanda ; Ricker, Lynette ; Ryckmans, Emmanuel ; Sacharewicz, Bozena ; Schockaert, Paul Alexandre ; Schoeberl, Eugenio ; Sendrey, Gérard ; Seroukh, Nouzha ; Settembrini, Franca ; Sledz, Miroslaw ; Sterckx, Daniel ; Tant, Charles ; Targa ; Thomas, Michel ; Tyminska, Honorata ; Vaudour, Frédéric ; de Vegaete, Marie-Josée Van ; Vincke, Pascale ; etc.
Geboorteplaats en -datum per kunstenaar
Historisch overzicht Art en Marge p. 280-283
Duits
Engels
Frans
Nederlands